Indiens ou paysans, peuples de la forêt ou de la montagne ? : vieux débats, nouvelles perspectives - Christian Gros (Caravelle)
This article tries to answer the following question : up to what point the creation of a generic ethnicity, brought about by Indian mobilization for the last thirty years in Latin America, is enough to go beyond the traditional division between low lands’ Indian populations and peasant Indian communities of the Andes.